2021
DOI: 10.2147/opth.s302224
|View full text |Cite
|
Sign up to set email alerts
|

“Double Prosthesis Implantation”: Biometry and Refractive Outcomes in Combined Intraocular Lens and Artificial Iris Surgery

Abstract: Purpose To assess the biometry and postoperative refraction in iris repair using ArtificialIris in combination with an intraocular lens (IOL). Setting Department of Ophthalmology, University Hospital Heidelberg, University of Heidelberg, Germany. Design Retrospective observational study. Methods We included 44 aniridic and aphakic eyes for IOL implantation in combination with iris prosthesis reconstruction. The iri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
9

Year Published

2021
2021
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 21 publications
0
10
0
9
Order By: Relevance
“…Although improving CDVA is not the primary objective when implanting an Artificial Iris, it has been shown that CDVA increases in some cases, 12 , 16 , 17 , 26 including two of the cases described, which is most likely due to simultaneous cataract surgery.…”
Section: Discussionmentioning
confidence: 91%
“…Although improving CDVA is not the primary objective when implanting an Artificial Iris, it has been shown that CDVA increases in some cases, 12 , 16 , 17 , 26 including two of the cases described, which is most likely due to simultaneous cataract surgery.…”
Section: Discussionmentioning
confidence: 91%
“…The implantation of an artificial iris is an effective option for the treatment of extensive traumatic iris defects and leads to an individual aesthetically appealing and good functional outcome as well as high patient satisfaction; however, this is an intervention that should not be underestimated because of a flat learning curve and various complications that can occur. [15,33]. Es wurde bereits in vitro an der optischen Bank (OptiSpheric IOL Pro II, Trioptics, Wedel, Deutschland) gezeigt, dass ein Annähen der IOL an die AI die optische Qualität nicht in einem relevanten Ausmaß reduziert [16].…”
Section: Discussionmentioning
confidence: 99%
“…In der klinischen Untersuchung zeigten sich am linken Auge neben der traumatischen Mydriasis und dem Irisdefekt bei 5 bis 7 Uhr eine Hornhautnarbe der unteren Hornhauthemisphäre sowie eine traumatische Katarakt. Fundoskopisch zeigten sich links periphe- [11].…”
Section: Befund Und Diagnoseunclassified